Estrategias de enseñanza-aprendizaje empleadas por docentes de la I.E. San Vicente del Distrito Especial de Buenaventura, en estudiantes del grado tercero con bajo rendimiento académico en las áreas de español y matemáticas - Fajardo Castaño, Angie (Universidad Antonio Nariño, 2021)
The main objective of this research work was to describe the teaching-learning strategies used by I.E. San Vicente of the Special District of Buenaventura, in the students of the third grade whit low academic performance in the areas of Spanish and mathematics. For this, postulates such as those of Díaz and Hernández (1998) who defined the pre-instructional, coinstructional and post-instructional strategies were taken into account. This research was approached with qualitative methodology, phenomenological design and descriptive scope. Regarding data collection, a semi-structured interview was used, which allowed us to conclude that the pre-instructional strategies implemented are motivational activities such as singing, storytelling, audiovisual resources, brainstorming, evaluation of previously seen topics, and the socialization of the objective of each class. Faced with co-instructional strategies, we found the activation of previous knowledge and experiences, promotion of meaningful learning, playful motivational activities such as drawing, painting, dynamics, association, repetition; and, regarding post-instructional studies, the evaluation was identified through dialogue, activities to be carried out at home and the call to parents for support with homework.